Global business negotiation - Sarkar, A.N. (New Delhi, 2010)
In past two decades, Globalization has activated and propelled the process of integration of nation economy with the global economy through virtual removal of all conceivable forms trade barriers across geopolitical boundaries. This, in turn, has opened-up enormous new vista of trade opportunities for international trading players and partners for business expansion ventures through multilateral contracts, deals and negotiations in all sectors of economy. Hence, to move on with the fast changing global economy the shape of things to come should be to resort to `Break-through negotiation` in most innovative, imaginative an challenging way to overcome cross-cultural and geopolitical barriers often confronted with in dealing global businesses. Within the broad parameters of this central theme, the Book on Global Business Negotiation provides a comprehensive treatise on the emerging concepts of global trade negotiations as are relevant and applicable in modern times to increasingly diverse, complex and hyper-competitive business environment. The book not only seeks to provide a broad framework of the processes, premises, various modalities as well as conditionality in which to conduct negotiations to eventually create a win-win situation; but also hopefully attempts to expose the readers to practical insights and live examples of successful negotiations that are actually happening in challenging business environment.
Keywords: Business negotiation